2018
DOI: 10.3390/molecules23123315
|View full text |Cite
|
Sign up to set email alerts
|

Chenodeoxycholic Acid from Bile Inhibits Influenza A Virus Replication via Blocking Nuclear Export of Viral Ribonucleoprotein Complexes

Abstract: Influenza A virus (IAV) infection is still a major global threat for humans, especially for the risk groups: young children and the elderly. The currently licensed antiviral drugs target viral factors and are prone to viral resistance. In recent years, a few endogenous small molecules from host, such as estradiol and omega-3 polyunsaturated fatty acid (PUFA)-derived lipid mediator protection D1 (PD1), were demonstrated to be capable of inhibiting IAV infection. Chenodeoxycholic acid (CDCA), one of the main pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
(41 reference statements)
1
14
0
Order By: Relevance
“…Since this increase in bile acids is most likely an active process rather than a passive reaction to an extreme state of illness, further basic research will need to elate on the beneficial effects of these alterations; some of which have already been described [13,33]. With regard to raised bile acids in general, it has been shown already, that LPS (lipopolysaccharide, an endotoxin from the outer membrane of gram-negative bacteria) and SIRS (systemic inflammatory response syndrome) in general decrease expression of the nuclear farnesoid-X receptor (FXR) [6,32]. This reduction of FXR increases expression of CYP7A1 (cytochrome-P 7A1) that increases to the production of new bile acids [20], which in turn are excreted into the serum by the basolateral efflux-pumps MRP3 and MRP4 [21] and can thus be measured elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Since this increase in bile acids is most likely an active process rather than a passive reaction to an extreme state of illness, further basic research will need to elate on the beneficial effects of these alterations; some of which have already been described [13,33]. With regard to raised bile acids in general, it has been shown already, that LPS (lipopolysaccharide, an endotoxin from the outer membrane of gram-negative bacteria) and SIRS (systemic inflammatory response syndrome) in general decrease expression of the nuclear farnesoid-X receptor (FXR) [6,32]. This reduction of FXR increases expression of CYP7A1 (cytochrome-P 7A1) that increases to the production of new bile acids [20], which in turn are excreted into the serum by the basolateral efflux-pumps MRP3 and MRP4 [21] and can thus be measured elevated.…”
Section: Discussionmentioning
confidence: 99%
“…CDCA was shown to inhibit some viruses, such as rotavirus [ 95 ]. Some in vitro studies also revealed that CDCA inhibits three different influenza A virus (IAV) strains, including the pathogenic H5N1 [ 78 ]. Treatment with CDCA resulted in a decrease in viruses both in infected A549 and MDCK cells.…”
Section: Probiotic-derived Metabolites As Beneficial Mediators In Viral Infection?mentioning
confidence: 99%
“…Treatment with CDCA resulted in a decrease in viruses both in infected A549 and MDCK cells. CDCA can block viral ribonucleoprotein (vRNP) nuclear export, impairing IAV replication in vitro [ 78 ].…”
Section: Probiotic-derived Metabolites As Beneficial Mediators In Viral Infection?mentioning
confidence: 99%
“…Previous studies have shown that stool samples from rCDI patients were enriched with taurocholic acid, a potent C. difficile germinant, and show decreases in LCA and DCA, secondary bile acids that inhibit C. difficile germination prior to FMT [ 63 , 64 ]. Interestingly, emerging evidence suggests that CDCA and secondary bile acid (tauroursodeoxycholic acid) may inhibit rotavirus, hepatitis B/D, and Influenza A, as well as Influenza A and hepatitis B virus infection, respectively [ 65 , 66 , 67 , 68 ]. Bile acids have been proposed to possess anti-inflammatory properties and can inhibit the NF-κB-dependent transcription of pro-inflammatory cytokines via farnesoid X receptor (FXR) and membrane G protein-coupled bile acid receptor Gpbar-1 (also known as TGR5) [ 69 ].…”
Section: Covid-19 and Fmt Efficacymentioning
confidence: 99%